NSAIDs in patients with viral infections, including Covid-19: Victims or perpetrators?. (July 2020) - Capuano, Annalisa; Scavone, Cristina; Racagni, Giorgio; Scaglione, Francesco; ,
Graphical abstract: Abstract: Taking anti-inflammatory drugs, including non-steroidal (NSAIDs), during Covid-19 infection, how much is risky? The French Minister of Health, who has raised an alarm on a possible risk deriving from the use of ibuprofen for the control of fever and other symptoms during the disease, opened the debate a few days ago. In this paper we examine available evidence from preclinical and clinical studies that had analysed the role of COX in the inflammatory process and the effects of NSAIDs in patients with infections. Most of the published studies that suggested not protective effects of NSAIDs were mainly performed in vitro or on animals. Therefore, their meaning in humans is to be considered with great caution. Based also on data suggesting protective effects of NSAIDs, we concluded that currently there is no evidence suggesting a correlation between NSAIDs and a worsening of infections. Further studies will be certainly needed to better define the role of NSAIDs and particularly COX2 inhibitors in patients with infections. In the meantime, we must wait for results of the revision started by the PRAC on May 2019 on the association ibuprofen/ketoprofen​​​​​​ and worsening of infections. Since nowadays no scientific evidence establishes a correlation between NSAIDS and worsening of COVID-19, patients should be advice against any NSAIDs self-medication when COVID-19 like symptoms are present.